AMINO ACIDS PROFILES OF MALE AND FEMALE MUDSKIPPER (Periophthalmus sp) - Wahbi, Moh; Karnila, Rahman; Edison, Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
The objective of the study was to obtain the chemical compositions and amino acids of male and female mudskipper (Periophthalmus sp). This study using the comparative experimental with  T-test consists of two treatments that was male and female mudskipper. The data was obtained presented in table form, analyzed descriptively and statistically with average standar deviation of the variables T1 and T2. The chemical characteristics of male and female mudskipper meat of water, ash, fat, protein, carbohydrate were 81.92, 80.00%; 10.21, 12.21%, 2.00, 2.04%; 86.68, 84.774%; 1.13, 1.01% (DW), respectively. Amino acids content on male and female mudskipper were 48.31, 42.88% (WW), respectively. The sex of fish has a significantly affect on the value of water, ash, fat, protein and amino acids content.